Inventory Of Small-Scale Fishing Units In Tanjung Solok Village, Kuala Jambi District, Tanjung Jabung Timur Regency - Lisna Lisna; M. Ridho Saputra; Eko Wiyanto; Afriani H; Muhammad Farhan; Fauzan Ramadan (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2022)
This study aims to identify and inventory the fishing units in Tanjung Solok Village, Kuala Jambi District, Tanjung Jabung Timur Regency. This research was conducted in June-July 2021. The method used in this study is a survey method, with direct observations in the field and conducting interviews with fishermen and noting the fishing units used by fishermen in Tanjung Solok Village. The sampling method is a census of 106 fishermen who have fishing units and domiciled in Tanjung Solok Village. The data collected in this study include general biographical data of fishermen, ships or boats used to catch fish, fishing gear used, and catches while fishing. The data analysis used in this research is Descriptive Data Analysis. Fishermen in Tanjung Solok are aged between 20 and 70 years with elementary, junior high and high school education and work as main fishermen, fishermen and side fishermen. The fishing vessels used are classified as outboard motor boats, non-motorized boats and motor boats made of fiber or wood with ship sizes of 1 to 4 GT. There are 7 types of fishing gear used, namely Gillnet, Mini Trawl, Pull Trawl, Splint, Rawai, Net, and Clam Stick and are dominated by fishing gear that is easy to operate and cheap. The most widely used fishing gear is the Gillnet. The fishing area for Tanjung Solok fishermen is around the territorial sea which is no more than 12 miles from the coastline because the fishing units are classified as small-scale. The fish caught by fishermen vary from shrimp and gulama fish, happy fish, side fish and shellfish.